Pandangan Kritis Amin Al-Khuli Terhadap Tradisi Balaghah Klasik - Shadiqul Wahdi; Raswan; Ahmad Dardiri (Indo Publishing, 2025)
This paper explores Amin al-Khuli’s critical perspective on classical Arabic rhetoric (balaghah), which he viewed as rigid, formalistic, and outdated in addressing modern communicative needs. In his seminal work Fann al-Qawl, al-Khuli redefined balaghah as the art of effective speech that emphasizes context, purpose, and rhetorical impact, rather than merely aesthetic structure. He advocated for integrating logical and aesthetic elements and expanded the function of declarative sentences to include expressive and emotional dimensions. Rejecting the traditional divisions of balaghah, al-Khuli proposed a more functional pedagogical structure covering words, sentences, paragraphs, and texts. His approach positions balaghah within a dynamic, humanistic framework, closely tied to lived experience and socio-cultural development. This study affirms that al-Khuli’s ideas offer a foundation for revitalizing balaghah as a relevant and applicable discipline in modern Arabic language education.